Exercise-induced hypohydration impairs 3 km treadmill-running performance in temperate conditions - Funnell, M. P.; Embleton, D.; Morris, T.; Macrae, H. Z.; Hart, N.; Mazzotta, T.; Lockyer, W.; Juett, L. A.; Mears, S. A.; James, L. J. (Journal of Sports Sciences, 2023)
Research assessing exercise-induced hypohydration on running performance in a temperate environment is scarce. Given the weight-bearing nature of running, the negative effects of hypohydration might be offset by the weight-loss associated with a negative fluid balance. Therefore, this study investigated the effect of exercise-induced hypohydration on running performance in temperate conditions. Seventeen intermittent games players (age 22 ± 1 y; VO2peak 52.5 ± 4.1 mL·kg-1·min-1) completed preliminary and familiarisation trials, and two experimental trials consisting of 12 blocks of 6 min of running (65% VO2peak; preload) with 1 min passive rest in-between, followed by a 3 km time trial (TT). During the preload, subjects consumed minimal fluid (60 mL) to induce hypohydration (HYP) or water to replace 95% sweat losses (1622 ± 343 mL; EUH). Body mass loss (EUH -0.5 ± 0.3%; HYP -2.2 ± 0.4%; P < 0.001), and other changes indicative of hypohydration, including increased serum osmolality, heart rate, thirst sensation, and decreased plasma volume (P = 0.022), were apparent in HYP by the end of the preload. TT performance was ~6% slower in HYP (EUH 900 ± 87 s; HYP 955 ± 110 s; P < 0.001). Exercise-induced hypohydration of ~2% body mass impaired 3 km running TT performance in a temperate environment.